On the Confraternities at the Church of the Holy Savior (St. Anthony the Abbot) in Zadar / O bratovštinama u crkvi Sv. Spasa (sv. Antuna opata) u Zadru - Zdenko Dundović (Miscellanea Hadriatica et Mediterranea, 2020)
Based on the original documents from the State Archives in Zadar and reports of apostolic visitors for Dalmatia from the 16th and 17th centuries, this paper analyzes the joining of Confraternity of Leather-Workers and Confraternity of St. Anthony the Abbot to the Church of the Holy Savior (subsequently renamed the Church of St. Anthony the Abbot) in Zadar: the documents analyzed indicate that the Confraternity of Leather-Workers moved to the Church of the Holy Savior earlier than the Zadar-based historian Carlo Federico Bianchi contends and that it certainly flourished under the auspices of this church earlier than the Confraternity of St. Anthony the Abbot. Contrary to Bianchi’s claims, this paper will prove that Confraternity of St. Anthony the Abbot joined the Church of the Holy Savior later than Confraternity of Leather-Workers and that the church was renamed the Church of St. Anthony the Abbot not earlier than in the 17th century. And finally, the paper will show that the interrelations and rights of the two confraternities at the Church of St. Anthony the Abbot were regulated by the Archbishop of Zadar and the apostolic visitor and reformer of Dalmatia, Ottaviano Garzadori.